P21-PARP-1 pathway is involved in cigarette smoke-induced lung DNA damage and cellular senescence. - Hongwei Yao; Isaac K Sundar; Vera Gorbunova; Irfan Rahman (PLoS ONE, 2013)
Persistent DNA damage triggers cellular senescence, which may play an important role in the pathogenesis of cigarette smoke (CS)-induced lung diseases. Both p21(CDKN1A) (p21) and poly(ADP-ribose) polymerase-1 (PARP-1) are involved in DNA damage and repair. However, the role of p21-PARP-1 axis in regulating CS-induced lung DNA damage and cellular senescence remains unknown. We hypothesized that CS causes DNA damage and cellular senescence through a p21-PARP-1 axis. To test this hypothesis, we determined the levels of γH2AX (a marker for DNA double-strand breaks) as well as non-homologous end joining proteins (Ku70 and Ku80) in lungs of mice exposed to CS. We found that the level of γH2AX was increased, whereas the level of Ku70 was reduced in lungs of CS-exposed mice. Furthermore, p21 deletion reduced the level of γH2AX, but augmented the levels of Ku70, Ku80, and PAR in lungs by CS. Administration of PARP-1 inhibitor 3-aminobenzamide increased CS-induced DNA damage, but lowered the levels of Ku70 and Ku80, in lungs of p21 knockout mice. Moreover, 3-aminobenzamide increased senescence-associated β-galactosidase activity, but decreased the expression of proliferating cell nuclear antigen in mouse lungs in response to CS. Interestingly, 3-aminobenzamide treatment had no effect on neutrophil influx into bronchoalveolar lavage fluid by CS. These results demonstrate that the p21-PARP-1 pathway is involved in CS-induced DNA damage and cellular senescence.